Development of an Easy-to-Use Tool for the Assessment of Emergency Department Physical Design - Majidi, Alireza; Tabatabaey, Ali; Motamed, Hassan; Motamedi, Maryam; Forouzanfar, Mohammad Mehdi (Archives of Academic Emergency Medicine, 2018)
Physical design of the emergency department (ED) has an important effect on its role and function. To date, no guidelines have been introduced to set the standards for the construction of EDs in Iran. In this study we aim to devise an easy-to-use tool based on the available literature and expert opinion for the quick and effective assessment of EDs in regards to their physical design. For this purpose, based on current literature on emergency design, a comprehensive checklist was developed.Â  Then, this checklist was analyzed by a panel consisting of heads of three major EDs and contradicting items were decided. Overall 178 crude items were derived from available literature. The Items were categorized in to three major domains of Physical space, Equipment, and Accessibility. The final checklist approved by the panel consisted of 163 items categorized into six domains. Each item was phrased as a â€œYes or Noâ€ question for ease of analysis, meaning that the criterion is either met or not. Â 